The Students’ Perceptions Toward the Use of Google Translate in English Writing Assignment - Maulidina, Yunita Putri; Budiastuti, Riana Eka; Wijayatiningsih, Testiana Deni (Universitas Muhammadiyah Semarang, 2024)
The continually advancing technology offers convenience across various educational domains, facilitating the process of writing in foreig languages. Google Translate, a widely embraced application for translating text into multiple languages, including English, stands out as a highly favored tool among university students for accomplishing their writing assignments. This study seeks to find out students' perspectives on using Google Translate in English writing assignments. Employing descriptive quantitative research, the study engaged approximately 50 college students with prior experience using Google Translate for English writing tasks. Data collection occurred through a combination of questionnaires and interviews. The findings from the questionnaire analysis revealed that 58% of the students affirmed agree with the significant effectiveness of Google Translate in enhancing their English writing skills. Positive responses also manifested in heightened confidence and the acquisition of new vocabulary among students utilizing Google Translate in their writing assignments, thereby contributing to the overall development of their writing proficiency.